China's Trade Patterns and International Comparative Advantage - Zhang, Xiao-guang (Palgrave Macmillan UK, 2000)
This book outlines the process of China's trade reforms over the past two decades and assesses the impact of these reforms on the economy. The author provides a detailed quantitative analysis to trace China's evolving commodity pattern of trade and changing comparative advantage structure over the entire reform period